Ink and inclusion: exploring appearance-based hiring bias, age differences, and their impact on respect, liking, and person-environment fit - Haviland, Molly (East Carolina University)
This thesis examines appearance-based hiring bias, focusing on the role of tattoos in influencing perceptions of job applicants. Specifically, it explores how age differences between participant (perceivers) and applicants (targets) affect evaluations of respect, liking, and person-environment fit, particularly in relation to perceptions of tattoos. Grounded in stigma theories and person-environment fit theories, this research aims to uncover whether tattoos, as a visible characteristic, exacerbate biases in hiring decisions and how these biases vary across age demographics. To test these relationships, a survey-based method will employ vignettes describing hypothetical job candidates, manipulating the presence or absence of tattoos and the age of the candidates to examine whether tattoo perceptions vary across different age groups. Results revealed that tattooed applicants were perceived as having significantly lower person-environment fit but unexpectedly higher liking, with no significant effect on respect. Age did not consistently moderate these relationships, though an interaction emerged for liking. Perceptions of workplace deviance and bias against younger individuals negatively influenced all outcome variables. A three-way interaction among tattoo presence, participant age, and applicant age did not significantly predict perceptions, though participant age influenced evaluations of older, non-tattooed applicants.
Keywords: Hiring Bias; Tattoos; Person-Environment Fit; Respect; Liking; Age Bias; Discrimination in employment; Tattooed people--Public opinion; Ageism; Work environment